1973
DOI: 10.1115/1.3451843
|View full text |Cite
|
Sign up to set email alerts
|

Gas Turbine Engine Mainshaft Roller Bearing-System Analysis

Abstract: An interdisciplinary systems analysis is presented for high-speed gas turbine engine mainshaft roller bearings which will enable the designer to meet the demands for ever higher rotative speeds and operating temperatures. The latest elastohydrodynamic experimental traction data are included. Analytical results cite a need for better definition of the rolling friction portion of the total traction. A fluid mechanics model for the detailed analysis of fluid drags is developed based upon a turbulent vortex-domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…6, 8, can be used for the accurate prediction of slip if the loss torque is known. Loss torque can often be extrapolated from past experience of similar installations, but where this is not possible there are a number of theoretical methods [8,9,10] which can be used. Unfortunately, empirical factors are still needed to account for the strong influence of the lubrication method, housing design and scavenge arrangement on loss torque.…”
Section: Methodsmentioning
confidence: 99%
“…6, 8, can be used for the accurate prediction of slip if the loss torque is known. Loss torque can often be extrapolated from past experience of similar installations, but where this is not possible there are a number of theoretical methods [8,9,10] which can be used. Unfortunately, empirical factors are still needed to account for the strong influence of the lubrication method, housing design and scavenge arrangement on loss torque.…”
Section: Methodsmentioning
confidence: 99%
“…It can be shown that the domain of 7 in equations (1) to (3) is -7, < 7 < 7, where T > = 2 arctan LJ2TOTC1^YHT=^] J (4) For small values of s (typically 0.1 for a high-speed roller bearing) and a relatively large value of c (say 0.7; the domain of c being 0 to 1), y x will be small. For instance, s = 0.1 and c = 0.7 give 7, = 3.6°.…”
Section: T =U C (R+r)cosy + Oi R Zcos(d + Y)mentioning
confidence: 99%
“…Several analytical models have been developed for the prediction of slip in roller bearings under different conditions [1][2][3][4][5][6]. Although reasonable agreement with experimental observations has been achieved for bearings operating under full elastohydrodynamic conditions, appreciable discrepancies can arise under high-speed and light load conditions.…”
Section: Introductionmentioning
confidence: 99%
“…So the research on cage's dynamic performance attracted the interest of many researchers. Harris [I] and Rumbarger [2] have established a quasi-static bearing analysis model to predict the skip-ratio the cage. Gupta, Meeks and Ghaisas [3] developed the dynamic model to research the instability of rolling element bearing's cage.…”
Section: Introductionmentioning
confidence: 99%